Work Engagement, Intrinsic Motivation and Job Satisfaction among Employees of A Coal Mining Company in South Borneo - Sartono, Hasan; Ardhani, Mauliah (Universitas Prasetiya Mulya, 2015)
This paper seeks to establish the relationships between three job characteristics constructs, namely work engagement, intrinsic motivation and job satisfaction in a workplace notorious for discord and conflict between workers and employers. A quantitative methodology was adopted using a cross-sectional survey. Respondents were selected from the workers at a mining company, with a final sample of 156 employees participating in the study. The Utrecht Work Engagement Scale, Intrinsic Motivation Inventory and the Minnesota Job Satisfaction Questionnaire were used to collect data. The results of the study indicate positive relationships between job satisfaction, work engagement and intrinsic motivation among the workers. Age and marital status were found to be significant contributors to workers’ job satisfaction, intrinsic motivation and work engagement. Implications of these results are that human resource interventions are required in order to deal with enhancing work engagement, intrinsic motivation and job satisfaction. Furthermore, the results indicate that intrinsic motivation and work engagement can enhance job satisfaction. The current study adds to the research pointing at job satisfaction as a promising underlying mechanism for employees’ to be internally motivated and engaged at work.